Indentifikasi IDENTIFIKASI PENYALAHGUNAAN JALUR SMS MARKETING DENGAN KONTEN SMS PREMIUM PADA PT DIAN PRIMA JAYARAYA DENGAN ALGORITMA NAIVE BAYES - william kohin cikutra; Susanto Hariyanto; Ellysha Kusuma; Raditya Rimbawan Oprasto (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2021)
PT Dian Prima Jayaraya is an SMS broadcast delivery service company in Indonesia, currently operators in Indonesia separate SMS channels into marketing and premium. The marketing channel is used for Promo/Marketing SMS and the Premium line is used for SMS that has a time period such as OTP. But in reality, many companies send premium content such as OTP in the marketing channel due to a lack of awareness of the content sent. The operator will impose sanctions on SMS that are misdirected, and the sanctions will be forwarded back-to-back to companies that use the services of PT Dian Prima Jayaraya. To avoid abuse, a classification model will be built using the Naives Bayes Algorithm, so that companies can identify misplaced content early to avoid fines from operators.